A comparison between CFD and thermal-structural analysis of structural steel members subjected to fire. (5th March 2021) - Alasiri, Muhannad R.; Mahamid, Mustafa
Abstract : Purpose: Standard fire resistance curves such as ASTM E119 have been used for so long in structural fire practice. The issue with use of these curves that they do not represent real fire scenarios. As a result, the alternatives have been to either conduct experiments or find other tools to represent a real fire scenario. Therefore, the purpose of this paper is to understand the temperature effects resulted from a designed fire on steel beams and whether the standard fire curves represent a designed fire scenario. Design/methodology/approach: Computational fluid dynamics (CFD) models were developed to simulate a designed fire scenario and to understand the structural responses on the beams under elevated temperatures. Consequently, the results obtained from the CFD models were compared with the results of three-dimensional (3D) non-linear finite element (FE) models developed by other researchers. The developed FE models were executed using a standard fire curve (ASTM E119). A parametric study including two case studies was conducted. Findings: Results obtained from performing this study showed the importance of considering fire parameters such as fuel type and flame height during the thermal analysis compared to the standard fire curves, and this might lead to a non-conservative design as compared to the designed fire scenario. The studied cases showed that the steel beams experienced more degradation in their fire resistance at higher load levels under designed fires. Additionally, the models used the standard fire curves underestimated the temperatures at the early stages. Originality/value: This paper shows results obtained by performing a comparison study of models used ASTM E119 curve and a designed fire scenario. The value of this study is to show the variability of using different fire scenarios; thus, more studies are required to see how temperature history curves can be used to represent real fire scenarios.